Exploring product–service systems in the digital era: a socio-technical systems perspective. Issue 4 (29th February 2020) - Li, Ai Qiang; Rich, Nicholas; Found, Pauline; Kumar, Maneesh; Brown, Steve
Abstract : Purpose: In the age of Industry 4.0, digital advancement is reshaping manufacturing models towards product–service systems (PSS). The drivers, readiness and challenges to move to a PSS model are not well understood, and the exploitation of the digital era presents the gap of this research. Design/methodology/approach: The research was conducted using semi-structured interviews in six manufacturers. Two forum debates were also conducted to supplement and validate the findings. Findings: Social and economic motivations rather than environmental considerations were driving the change to PSS. Digital technologies could be an important driver if manufacturers reached a certain PSS maturity level. A high level of technical readiness was offset by a low level of social investments and the strategic development of human resources. Value co-creation was a main challenge though manufacturers had the advantage of digital connectivity, which indicated new human requirements; the greater the enabling power of digital technologies, the greater the need for advanced human skills. Practical implications: Human resource management has underpinned lean models; yet, the role of employees within PSS is underdeveloped despite the impact of staff in exploiting digitalisation and value co-creation. A "learning organisation" and socio-technical fit are required for the "diffusion of innovation" of PSS. Originality/value: This research attempted to explore drivers, readiness and challenges for PSS from a socio-technical systems (STS) perspective. Three levels of PSS maturity with STS features were derived from the research, providing guidance for manufacturers.